Schistosomiasis endemicity and its role in sexually transmitted infections – a systematic review and meta-analysis - Asare, Kwame Kumi; Afful, Philip; Abotsi, Godwin Kwami; Adu-Gyamfi, Czarina Owusua; Benyem, George; Katawa, Gnatoulma; Arndts, Kathrin; Ritter, Manuel (Frontiers in Parasitology, 2024)
Introduction: Schistosomiasis, a tropical parasitic disease, affects 779 million people globally, with 85% of cases in Africa. The interplay between schistosomiasis and other sexually transmitted infections (STIs) can exacerbate health burdens, but most attention has focused on interactions with HIV, neglecting coinfections with other STIs. This systematic review and meta-analysis aims to understand the role Schistosoma infections play in STIs within schistosomiasis-endemic populations.The study is a systematic review and meta-analysis investigating the link between Schistosoma infections and sexually transmitted infections (STIs) in endemic regions. It uses PRISMA guidelines, electronic databases, and Google Scholar to assess prevalence, associations, and heterogeneity, reducing bias using a Meta-Mar statistical tool.Results: A quantitative synthesis of 33 articles from 1975-2024 involved 22,587 participants from 13 countries, including regions in Africa, France, and China, examining coinfections of schistosomiasis and sexually transmitted infections (STIs), including HIV. The pooled estimates showed a significant risk association between schistosomiasis and STIs (RR (95% CI)= 1.18, (1.13-1.24); z/t = 7.55, p<0.0001) using a fixed effect model. Cochran's Q test (Tau 2 = 0.5061, Chi^2 = 476.65, df = 32, p<0.01) indicated significant heterogeneity. The Higgins I 2 statistic of 93.0% (91.5%-94.7%), H = 3.86 (3.43-4.33), highlighted substantial variance between studies. Subgroup analysis showed West Africa (Weight IV = 1.7%, RR (95% CI) = 1.78 (1.28-2.47), I 2 = 59%), East Africa (Weight IV = 10.5%, RR (95% CI) = 0.99 (0.86-1.13), I 2 =54%), and Southern Africa (Weight IV = 82.0%, RR (95% CI) = 1.16 (1.10-1.21), I 2 = 97%) contributed significantly to the high heterogeneity in the pooled analysis. Females had a notably higher risk of STIs in the context of schistosomiasis (k=17, RR: 1.30, 95% CI: 1.23-1.37, Q=316.78, I²=94.9%), compared to males (k=6, RR: 0.94, 95% CI: 0.77-1.15, Q=53.44, I²=90.6%) and the combined group of females and males (k=9, RR: 0.95, 95% CI: 0.88-1.02, Q=16.38, I²=50.2%).The study found a high risk of coinfections between schistosomiasis and STIs, particularly in West and Southern Africa, confirming Female genital schistosomiasis as a major risk for STIs.